2020
DOI: 10.1063/1.5142264
|View full text |Cite
|
Sign up to set email alerts
|

Reliable inkjet contact metallization on printed polymer semiconductors for fabricating staggered TFTs

Abstract: Even though the fundamental benefits of the staggered bottom-gate top-contact geometry in organic thin-film transistors (TFTs) have been fully demonstrated for enhancing the charge injection efficiency, most printed organic TFTs with inkjet-printed source/drain electrodes have only been fabricated in bottom-contact configurations, probably due to the difficulty of printing with metal-nanoparticle ink on soluble organic semiconductor (OSC) without film deformation/dissolution. Here, we present the printing proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Active-matrix sensor arrays based on printed TFT arrays are also rare (Table S3). In addition to our previously developed fundamental inkjet printing design rules, the advanced design rule for large-area electronic devices and delicately optimized fabrication process in this work made it possible to develop ultrathin (2 μm) TFT arrays with a 100% yield and high uniformity (RSD < 10%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Active-matrix sensor arrays based on printed TFT arrays are also rare (Table S3). In addition to our previously developed fundamental inkjet printing design rules, the advanced design rule for large-area electronic devices and delicately optimized fabrication process in this work made it possible to develop ultrathin (2 μm) TFT arrays with a 100% yield and high uniformity (RSD < 10%).…”
Section: Resultsmentioning
confidence: 99%
“…The cartridge and platen temperatures were set at 40 and 50 °C, respectively. Layout-to-bitmap conversion and design rules are explained in our previous works, and their extension into large-area arrays is described in Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, the authors discussed a charge injection efficiency of AgNP contacts by comparing thermally evaporated Ag contacts. The results showed a comparable contact resistance in inkjet-printed staggered TFTs by the use of directly printed S/D electrodes on a conjugated polymer . The authors recently developed nonvolatile TFT-based memory devices fabricated by using the fab process discussed in this paper .…”
Section: Related Workmentioning
confidence: 72%
“…The results showed a comparable contact resistance in inkjet-printed staggered TFTs by the use of directly printed S/D electrodes on a conjugated polymer. 51 The authors recently developed nonvolatile TFT-based memory devices fabricated by using the fab process discussed in this paper. 13 The authors believe that their previous reported results demonstrate the reliability and the extendibility of the current study to the fabrication of flexible LSI system applications.…”
Section: ■ Related Workmentioning
confidence: 99%
“…Nevertheless, most OTFTs have been fabricated in BC configurations because of the process difficulty of making source/drain (S/D) metal electrodes on top of the organic semiconductor layer with precise patterning [30,31]. Recent advances on inkjet contact metallization on printed polymer semiconductors can reverse this trend in favor of staggered TFTs [32]. In order to be prepared for this scenario, a proper model to describe the staggered configuration is necessary, despite it being more complex model with more parameters.…”
Section: Introductionmentioning
confidence: 99%